Islam in retrospect : recovering the message - Mahmasani, Mahir (United States : Olive Branch Press, 2014)
Islam, in many of its current guises, no longer resembles its original Message. In a world of intractable conflicts plagued by political Islam and Islamophobia and where other forms of fundamentalism within the major religious creeds are on the rise, as well this book serves as a reminder. It aims to recover and reaffirm Islam's underlying and guiding principles. Setting out to distinguish the divine from the human in order to elucidate the pristine nature of the divine Message, Mahmassani reasserts Islam's universal, secular, and progressive character. In Part One of this comprehensive.
Islam, in many of its current guises, no longer resembles its original Message. In a world of intractable conflicts plagued by political Islam and Islamophobia and where other forms of fundamentalism within the major religious creeds are on the rise, as well this book serves as a reminder. It aims to recover and reaffirm Islam's underlying and guiding principles. Setting out to distinguish the divine from the human in order to elucidate the pristine nature of the divine Message, Mahmassani reasserts Islam's universal, secular, and progressive character. In Part One of this comprehensive.
Cover; Title Page; Copyright; Dedication; Contents; Acknowledgments; Preface; Introduction: Myths and Changing Realities; Part One: The Universal Nature of Islam; Chapter 1: Islam Did Not Appear in a Vacuum; Chapter 2: The Holy Qur'an as the Essential Source of Islam; Chapter 3: The Nature and Role of Prophetic Tradition; Chapter 4: The Scope of the Universal Nature of Islam: Issues of; Part Two: The Secular Nature of Islam; Chapter 5: Defining Secularism; Chapter 6: Divine Governance and Human Government; Chapter 7: The Evolution of the Islamic State. Chapter 8: Islam and the Myth of a Divine Theory of StateChapter 9: Islam and Shari'a; Chapter 10: Humanism and Individualism in Islam; Part Three: The Progressive Nature of Islam; Chapter 11: The Concept and Scope of Progressivism in Islam; Chapter 12: Islam and the Mind; Chapter 13: Islam and'Others'; Chapter 14: The Right to Equality; Chapter 15: The Right to Freedom; Chapter 16: Reflections on Human Rights in Islam; Conclusion; Notes; Glossary; Bibliography.
Includes bibliographical references (pages 769-788) and index.
Sumbangan Mohamad Taha (2017).
Keywords: Islam -- Essence, genius, nature; Islam -- Universality